INFLUENCE OF PLANNING, IMPLEMENTATION AND SUPERVISION TO CUSTOMER SATISFACTION THROUGH QUALITY TANJUNG GELAM PORT SERVICES KARIMUN DISTRICT - Handayani, Evi; Indrayani, Indrayani; Khaddafi, Muammar; Wibisono, Chablulah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This research was conducted by distributing 290 questionnaires. Discussion of the results of field studies to obtain data on answers to questionnaires that measure five main variables in this study, namely Planning, Implementation, Monitoring, Customer Satisfaction and Service Quality. The results of the analysis and discussion using the SEM-PLS (Structural Equition Modeling-Partial Least Square) method using the R-Square test and hypothesis testing, namely direct and indirect effects. The path coefficient calculation in this study is assisted by Smart PLS Ver 3.0. to determine the direct and indirect effect between variables. Planning (X1) has a significant positive effect on Service Quality (Z), with a t-statistics value of 2.660 > 1.96 and a p-value of 0.008 < 0.05, the hypothesis is accepted. Implementation (X2) has a significant positive effect on Service Quality (Z), with a t-statistics value of 2.415 > 1.96 and a p-value of 0.016 < 0.05, the hypothesis is accepted. Supervision (X3) has a significant positive effect on Service Quality (Z), with a t-statistics value of 2.715 > 1.96 and a p-value of 0.000 < 0.05, the hypothesis is accepted. Service Quality (Z) has a significant positive effect on Customer Satisfaction (Y), with a t-statistics value of 2.218 > 1.96 and a p-value of 0.020 < 0.05, the hypothesis is accepted. Planning (X1) has a significant positive effect on Customer Satisfaction (Y), with a t-statistics value of 2.657 > 1.96 and a p-value of 0.012 < 0.05, the hypothesis is accepted. Implementation (X2) has a significant positive effect on Customer Satisfaction (Y), with a t-statistics value of 2.036 > 1, 96 and the p-value is 0.002 <0.05, the hypothesis is accepted. Monitoring (X3) has a significant positive effect on customer satisfaction (Y), with t-statistics 2.183 > 1.96 and a p-value of 0.000 <0.05, the hypothesis is accepted.